The Influence of Social Media Marketing on Brand Loyalty - MOKHTARUDDIN, SURAYA AKMAR; KHALID, NOR RAHIMY; MOHD AZMI, MOHD RIZAL (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
Information technology advancement has given an impact to the customers experience in service as well as their relationship with the service provider. The flexibility of communication channels such as smartphones, social media, email, Facebook, twitter, and others in making it easier for firm to effectively deliver message to target customer. The impact of social media marketing on band loyalty has been widely studied by previous literature in various contexts. However, the empirical research from the apparel company context is still limited. Therefore, this conceptual paper is proposed to fill in the social media marketing literature by focusing on the relationship between social media marketing and brand loyalty from the customer perspective. Academically, this study contributes to the literature of social media marketing in business-to-customer context specifically from customer point of view and practically to the apparel company in comprehending social media marketing in enhancing brand loyalty in apparel industry